Penanggulangan Transformator Distribusi Berbeban Lebih Dengan Metode Sisip Trafo Pada Penyulang PW-02 PT PLN (Persero) ULP Subulussalam Kota - Filia Berkat Nanda Lumbantobing; Hamdani (Jurnal Nasional Teknologi Komputer, 2026)
Distribution transformer is one of the most important components in the distribution of electric power from distribution substations to customers. Distribution transformers that experience loads exceeding 80% of the transformer capacity will affect the life of the distribution transformer and can also affect the level and quality of service to consumers and have the potential for disruption. Therefore, it is necessary to take action so that the percentage of distribution transformer loading does not exceed the transformer capacity by installing an Insert Transformer. At PT. PLN (Persero) ULP SUBULUSSALAM KOTA, there is a transformer that experiences overloading that occurs at the SKI072-00 Distribution Substation of 96.016% and after the Insert Transformer is installed, the loading at the SKI072-00 substation becomes 43.27%. This proves that the installation of an Insert Transformer is a fairly good method for overcoming overload disturbances at the SKI072-00 Substation, so that it can extend the life of the transformer, improve the quality of service to customers and reduce the potential for disturbances because the transformer loading below 80% can work well.